Prevention of Liver Injury by Moringa oleifera aqueous leaf extract in rats treated with isoniazid and rifampicin - Balaraba, Bello; Muhammad, Wudil A. (Pharmacognosy Communications)
Background: Moringa oleifera has been reported to have a lot of therapeutic potential such as antidiabetic, hypocholesterolemic and hypotensive. Objective: This work was undertaken to study the effects of pretreatment and co-administration of aqueous extract of Moringa oleifera leaves on anti-tubercular drug hepatotoxicity in rats. Materials and Methods: Wistar albino rats were divided into six groups of three rats each. Group A was normal control. Group B was the test control administered with anti-tubercular drugs isoniazid (27 mg/kg bw) and rifampicin (54 mg/kg bw) to induce liver damage. Groups C and D were pretreated with 100 mg/kg bw and 200 mg/kg bw of the extract for four weeks, then administered with isoniazid and rifampicin at doses 27 mg/kg bw and 54 mg/kg bw, respectively for same duration. Groups E and F were administered with the same doses of the extracts and anti‑tubercular drugs concurrently for four weeks. Serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP) and unconjugated bilirubin (uBIL) were analysed to determine the effect of the extract on hepatotoxicity caused by the drugs. Results: Oral pretreatment and co-administration of aqueous extract of Moringa oleifera leaves significantly (P ≤ 0.05) reduced serum ALT, AST and ALP activities, and uBIL concentration compared to the test control. Conclusion: The results suggest the potential protective effect of aqueous extract of Moringa oleifera on anti-tubercular drug hepatotoxicity in rats.
Keywords: hepatotoxicity; isoniazid; liver damage; Moringa oleifera; rifampicin